Impact of Government Expenditure on Public Primary Schools Teachers’ Welfare in Jos South Local Government Area of Plateau State, Nigeria - Azi, , A. S.; Shikdima,, V. A. (Kashere Journal of Education, 2021)
This study examined the impact of Government expenditure on public primary school teachers’ welfare in Jos-South Local Government Area of Plateau State, Nigeria. One research question was answered to achieve the objective of the study. Descriptive survey design was employed for the study. The population of the study consisted of 36 supervisors and 139 teachers in public primary schools in the study area. The sample size was made up of 27 supervisors and 91 teachers. Multi stage sampling technique was employed for selecting the sample. The instruments for data collection were self-structured questionnaires titled Government Expenditure and Primary Education Development Questionnaire for Teachers (GEPEDQT) and Government Expenditure and Primary Education Development Questionnaire for Supervisors (GEPEDQS). The reliability of the instrument was established using Cronbach alpha method which yielded 0.89 and 0.87 respectively, it was found to be reliable. The study employed the use of mean and standard deviation in analysing the data. Findings from the research question indicated that government expenditure for teachers’ welfare in public primary schools in the study area was inadequate. Based on this finding, it was recommended among others that government should increase the expenditure of the educational sector in line with the recommendations of United Nations Educational, Scientific and Cultural Organization (UNESCO) which is 26 percent for developing countries.